Two decades on the MACBETH approach: a bibliometric analysis - Ferreira, F.; Santos, S. (Annals of Operations Research, 2021)
MACBETH stands for measuring attractiveness by a categorical based evaluation technique. It is a multiple criteria decision analysis technique created by Carlos Bana e Costa and Jean-Claude Vansnick in the early 1990s. Due to both the increasing application of the technique and progress achieved to date, this study aims to conduct a bibliometric literature review on MACBETH. The database for the review contains 192 scientific articles published in scholarly publications indexed in the Scopus database from 1994 to 2016. Although other literature reviews of the technique exist, this study has a different emphasis and uses two distinct citation analysis methods—bibliographic coupling and co-citation—, allowing us to generate new insights regarding some of the most active and influential articles, journals and authors, as well as to reveal rankings, clusters of contributions and collaboration networks. The results obtained are important to enhance our understanding of the technique’s anatomy (i.e., its intellectual structure), and can support the identification of new lines of application and development.